Analisis Pengaruh Kualitas Produk Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Dalam Membentuk Loyalitas Pelanggan Pada Rumah Makan Di Kota Solo - Sulistianto, Wahyu, Dr. Anton Agus Setyawan, SE.,MSi (2016)
The purpose of this study was to analyze the impact of quality product (X1) and service quality (X2) towards consumer satisfaction (Y) in the form of customer loyalty restaurant in town solo. The population in this study are all the people who've used the services of a solo diner and sample in this research that people who are and have used the services of the restaurant in solo. The sampling technique used is convenience sampling by taking the 150 respondents who easily found. The study used regression analysis tiered or path analysis. This study resulted in several findings that the regression analysis of the first quality of the product has no significant effect on customer satisfaction. Second, the quality of service significantly influence customer satisfaction. Regression analysis of two paths, yielding findings that. product quality has no significant effect on customer loyalty. The service quality significantly influence customer loyalty and customer satisfaction also has no significant effect on customer loyalty.